2020
DOI: 10.3390/ma13051237
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Styrene–Maleic Anhydride Copolymer Compatibilized Polyamide 66/Poly (Phenylene Ether) Blends: Effect of Maleic Anhydride Concentration and Copolymer Content

Abstract: Polyamide 66 (PA66)/poly (2,6-dimethyl-1,4-phenylene ether) (PPE) blends with a ratio of 50/50 (w/w) were produced by a twin-screw compounder. The immiscible blends were compatibilized using two different styrene–maleic anhydride copolymers (SMA) with a low (SMAlow) and a high (SMAhigh) maleic anhydride (MA) concentration of 8 and 25 wt%, respectively. Furthermore, the SMA content was varied from 0 to 10 wt%. The influence of MA concentration and SMA content on the morphological and thermomechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A morphology transition is mainly induced either by a change in blend ratio or by a shift of the viscosity ratio between the dispersed and matrix phases [53,54]. For a constant blend ratio, a shift in the morphology induced by SMA copolymers was already reported elsewhere [47]. Inclusions within the PA66 phase, only apparent when SMA was added, leads to an increase of the PA66 viscosity, thus shifting the viscosity ratio between PA66/SMA and PPE to closer values.…”
Section: Pa66/ppementioning
confidence: 53%
See 2 more Smart Citations
“…A morphology transition is mainly induced either by a change in blend ratio or by a shift of the viscosity ratio between the dispersed and matrix phases [53,54]. For a constant blend ratio, a shift in the morphology induced by SMA copolymers was already reported elsewhere [47]. Inclusions within the PA66 phase, only apparent when SMA was added, leads to an increase of the PA66 viscosity, thus shifting the viscosity ratio between PA66/SMA and PPE to closer values.…”
Section: Pa66/ppementioning
confidence: 53%
“…It seems that the SMA's compatibilizing mechanism is based on an emulsification of the PPE domains, revealing nano-sized droplets by pinch-offs as a result of surface roughening of the PPE phase [14,16,55]. In our previous work [47], we reported that the small droplets either consist of PA66-g-SMA micelles (smaller 50 nm) or more likely PA66-g-SMA micelles swollen by PPE (larger 50 nm). Up to now, no analysis was done to confirm the theory of swollen micelles for PA-based PPE blends.…”
Section: Pa66/ppementioning
confidence: 80%
See 1 more Smart Citation
“…Then, the most evident effect of compatibility is the presence of bonds at the interface, resulting in an increased stiffness and a decreased deformability of the matrix. This effect was observed in several cases, as an example in polyamide blends [ 41 , 42 ], polyester [ 43 ], or polycarbonate [ 9 , 44 ] based blends. Interestingly, the addition of C1 to pAC gave the best value of tensile strength, probably because of the achievement of a good balance between increased stiffness and deformability of the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The PPS/PPO blends showed extraordinary impact strength values (maximum of 63.6 kJ/m 2 ), higher than those of common blends by 10 folds. Aksit, Zhang et al 29,30 found that PA66/PPO blends can effectively be compatibilized using SMA and HIPS-g-MAH, increased the elongation at break of the blends by 70%, and 65%, respectively, effectively improved the toughness of the blends. Bin et al 26 studied HDPE/PPO blends and used SEBS as a compatibilizer to improve the properties of blends.…”
Section: Introductionmentioning
confidence: 99%